Use of a halo frame for optimum intra- and post-operative management after scalp replantation/revascularization - R. Koul Ashok; Sushil Nahar; Beena Valandi; Praveen H. P. Kumar (Indian Journal of Plastic Surgery)
We present a new technique for stabilizing an avulsed scalp during and after replantation/revascularization. We used an aluminium "halo" frame with 4 screws. This technique can rigidly stabilize an avulsed scalp and eliminate the possibility of shearing/pressure necrosis. This device can make perioperative management easier and more comfortable for the patient and caregivers.